1982
DOI: 10.1177/140349488201000102
|View full text |Cite
|
Sign up to set email alerts
|

Unemployment and Hospitalization among Bricklayers

Abstract: 677 active members of the bricklayers' trade union in Aarhus have been investigated with regard to unemployment and hospitalization during the period April 1, 1972-March 31, 1978. Information concerning unemployment was obtained through the bricklayers' trade union, and information about hospitalization from the hospital administration registry of three counties of Northern Jutland and from the Danish Central Psychiatric Register. Using logit analysis it was found that admission to a hospital increased the ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…A review by Dooley, Fielding and Levi [9] found that unemployment was associated with biomarkers of poor health such abnormal disturbances in cortisol levels [10], increased cholesterol [11] and impaired immune reactions [12], as well as unhealthy behaviours such as excessive alcohol consumption [13,14] and smoking [15]. In addition, mental health indicators such as depression [16], psychiatric admissions [17,18] and suicide [19-22] are correlated with unemployment. Research has similarly shown that those in poor quality or stressful jobs generally have worse physical and mental health than those in good quality work [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…A review by Dooley, Fielding and Levi [9] found that unemployment was associated with biomarkers of poor health such abnormal disturbances in cortisol levels [10], increased cholesterol [11] and impaired immune reactions [12], as well as unhealthy behaviours such as excessive alcohol consumption [13,14] and smoking [15]. In addition, mental health indicators such as depression [16], psychiatric admissions [17,18] and suicide [19-22] are correlated with unemployment. Research has similarly shown that those in poor quality or stressful jobs generally have worse physical and mental health than those in good quality work [23,24].…”
Section: Introductionmentioning
confidence: 99%